Women's health: Preventive measures for cervical cancer (Research, Society and Development, 2021)
The study aims to understand the risk factors for cervical cancer, and to describe preventive measures for the disease. It is an integrative literature review, with a qualitative approach, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS). The inclusion criteria include literature review surveys available in the databases described, between the years 2010 to 2020. As exclusion criteria, articles were not considered for monetary compensation, incomplete and not converging with this study. For data collection, 10 articles and 02 studies referring to health entities were analyzed. The results show that the risk factors for cervical cancer include the early onset of sexual practices, multiple intimate partners, infectious and reactive conditions, active and passive smoking, prolonged use of oral contraceptives, and nutritional deficiencies. We conclude the importance of the perception of health professionals working in Primary Health Care units, facing the guidelines regarding preventive measures for uterine cancer, aiming to promote welcoming care practices, and a qualified perception to meet this demand, enabling the initial reception, comprehensive, assistance and humanized monitoring.